Entrepreneurship: an innovative path in Nursing (Research, Society and Development, 2020)
Nursing has great reasons and opportunities to start your own business. At first, because it is a service associated with a clear and comprehensive view of reality, that is, an identification of the needs of the human race as a whole. Still, because nursing is qualified and has chances to analyze new areas with regard to the social, without necessarily submitting to the gaps already seen as deserving of care in which, in large cases, the notion of illness dominates. The study aims to analyze the trend of scientific publications on entrepreneurship as an innovative path in Nursing. It is an integrative literature review, the research was done through online search in the bases: Online System of Search and Analysis of Medical Literature (MEDLINE) PubMed, Latin American and Caribbean Literature in Health Sciences (LILACS) and Base of Nursing Data (BDENF), Scidentific Electronic Library Online (SCIELO), with the descriptors: entrepreneurship AND entrepreneurs AND entrepreneur, entrepreneurship AND entrepreneurial initiative AND risk contract AND nursingAND nurse. The studies were grouped in two categories, according to their similarity: Motivation of the nurse for entrepreneurship and profile of the entrepreneur nurse. In conclusion, the entrepreneur nurse is the individual who identifies opportunities and in an innovative, creative way, manages to create something new, whether of social value or not, calculating risks and generating the necessary resources. Nursing has many ways of using its knowledge and developing new types of services, building its own enterprise. The nurse is a professional whose skills and competences are understood and developed in their training. There is also a need for nurses to act differently in view of the possibility of entering the job market, or in situations already experienced.